Suzuki Early Childhood Education: um estudo dos seus conteúdos sob a perspectiva de Zabala e a relação com a filosofia Suzuki - Alvarenga Giglioti, Gabrielle (Universidade Federal de São Carlos, 2025)
This thesis investigates the content covered in early childhood music education classes from the perspective of the Suzuki Philosophy, which values not only musical training but also the holistic development of the individual. The main aim of the research is to understand the content developed in the Suzuki Early Childhood Education (SECE) program classes, identify the activities, and analyze their relationship with the principles of the Suzuki Philosophy. To achieve this, the research seeks to: (1) identify the content covered in the classes; (2) analyze the relationship between the activities carried out and the Suzuki Philosophy; and (3) understand how these contents are taught to infants and young children. The study adopts a qualitative approach and a case study design, using semi-structured interviews, participant observations, and document analysis to collect and interpret data. The content analysis is based on Zabala's categorization, which distinguishes procedural, attitudinal, and conceptual content. The results indicate that procedural content, especially that which is more motor and algorithmic in nature, predominates in the classes, reflecting Suzuki's principle of learning through repetition and practical experimentation. Attitudinal content, particularly related to norms and values, highlights the emphasis of the Suzuki Philosophy on character formation. Conceptual content appears more sporadically, mainly in the form of teacher explanations in specific situations. The research concludes that the activities in the SECE program align with the principles of the Suzuki Philosophy, as each principle appears to varying degrees in different activities observed during the classes. Additionally, the teacher’s role in applying these principles is emphasized, particularly focusing on procedural and attitudinal content. Therefore, the analysis suggests that criticisms of the Suzuki Method often stem from its practical implementation, which is frequently carried out without proper training and application of the Suzuki Philosophy.
Suzuki Early Childhood Education:: a study of its contents from Zabala's Perspective and Its relationship with the Suzuki Philosophy
Keywords: Método Suzuki; Suzuki Early Childhood Education; Musicalização; Conteúdos; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA; CIENCIAS HUMANAS::EDUCACAO::CURRICULO